Penerapan Quizizz Sebagai Media Evaluasi Interaktif Untuk Meningkatkan Motivasi Belajar Mahasiswa - Ayu Ismi Hanifah; Nawafilah, Nur Qomariyah (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Active learning is one of the strategies used to create a fun learning atmosphere and increase student activity. One strategy that can be done is by implementing interactive media. Quizizz is an interactive game-based media that can provide a learning experience so that students are directly involved and can be used as an interactive learning evaluation media. In addition to being an evaluation media, Quizizz can build engagement between students and the media so that students are motivated to be more active. This study aims to analyze the implementation of Quizizz as an interactive evaluation tool to enhance students' learning motivation. This study uses a quantitative descriptive research method. The instruments used in this study include observation sheets, learning motivation questionnaires, and quizzes on Quizizz. The results of this study indicate that the evaluation results obtained by implementing Quizizz as many as 74.3% of students scored above 68 which is included in the good assessment category. In addition, as many as 78% of students are motivated by the application of Quizizz because it creates a competitive and fun learning atmosphere.